Study of The Effect of Adding a Blend of Engineering Polymers on the Rheological Modifications of Sulfurated Asphalt - Mahmoud Abass; Ammar amdoon (College of Education for Pure Sciences, 2021)
In this study, a mixture of two polymers consisting of commercial adhesive [ethylene vinyl acetate (EVA)] and melamine (M) Which were used in this study. Different weights of both polymers were used with total weights equal for (1 g). The asphalt was treated with the above mixture in the presence of 1% by weight of sulfur at (180 ° C) for one hour. The rheological properties of the modified samples and original one were measured, which included measuring the ductility , penetration, and softining point as well as calculating the penetration index and percentage of the separated asphaltens . After that, the best samples obtained from the above modification process were taken, and several interactions were performed on it in order to determine each of : The optimum conditions for the conversion process have been established and include the percentage of added sulfur and the temperature the best time, the best weights of the mixture, and the best addition sequence. After that, the best sample obtained from this study was taken and the marshals test with chemical immersion was performed, as well as the effect of aging on this sample was studied. The study gave good results in the field of asphalt resistance to the deformation processes which were carried out on it.